Career understanding, motivation, and students' decision-making to choose vocational high school (SMK) in non-industrial area - MS, Hery Wiharja; Firnanda, Ary (Jurnal Pendidikan Teknologi Kejuruan, 2021)
This study aims to measure and describe students' decision-making to choose Vocational High School (SMK) in terms of their career understanding and motivation. The subjects of this study were 135 Year 9 students in five SMK throughout Southwest Aceh Regency. The total sampling method was used to choose the subjects from the entire population. Furthermore, the data were analysed using correlation analysis between variables partially and simultaneously with ANOVA (F test). The results of the partial correlation analysis show that the career understanding variable has a significant influence on students' decision-making to choose SMK with rcount = 0.411 at a significance level of 0.05. In addition, the motivation variable also has a significant influence on decision-making to choose SMK with rcount = 0.375. Simultaneously, career understanding and motivation significantly affect choosing SMK with Fcount = 19.850 and Ftable = 3.06 (Fcount > Ftable). This study results indicate that career understanding variables consist of work planning, work exploration and knowledge of the world of work. In contrast, the motivation variables consist of intrinsic and extrinsic motivation, which could be the basis for students' decision making